Transparent ceramics of yttrium-aluminum garnet (Y₃Al₅O₁₂) from nanocrystalline powders obtained by co-precipitation - Baumer, V.N.; Vovk, E.A.; Vovk, O.M.; Deineka, T.G.; Kosmyna, M.B.; Mateychenko, P.V.; Puzikov, V.M.; Sergienko, Z.P.; Tolmachev, A.V.; Shekhovtsov, A.N.; Yavetskiy, R.P. (Functional Materials, 2008)
Nanosized powders of yttrium-aluminum garnet Y₃Al₅O₁₂, (YAG) have been obtained by chemical co-precipitation. The effect of the powder structure and morphology on the compactibility and sinterability has been studied. The optimal combination of these properties has been found in the YAG powder having the average grain size of 80 nm synthesized at 1200°C. Using the vacuum sintering at 1750°C, the transparent Y₃Al₅O₁₂ ceramics has been obtained having the density 99.9% of theoretical value and the transmission coefficient 60% in the wavelength range of 400 to 800 nm.